Survival in primary hemophagocytic lymphohistiocytosis, 2016 to 2021: etoposide is better than its reputation - Böhm, Svea; Mauz-Körholz, Christine; Wustrau, Katharina; Pachlopnik Schmid, Jana; Prader, Seraina; Ahlmann, Martina; Yacobovich, Joanne; Beier, Rita; Speckmann, Carsten; Behnisch, Wolfgang; Ifversen, Marianne; Jordan, Michael; et al. (Blood, 2024)
Primary hemophagocytic lymphohistiocytosis (pHLH) is a life-threatening hyperinflammatory syndrome that develops mainly in patients with genetic disorders of lymphocyte cytotoxicity and X-linked lymphoproliferative syndromes. Previous studies with etoposide-based treatment followed by hematopoetic stem cell transplantation (HSCT) resulted in 5-year survival of 50% to 59%. Contemporary data are lacking. We evaluated 88 patients with pHLH documented in the international HLH registry from 2016-2021. In 12 of 88 patients, diagnosis was made without HLH activity, based on siblings or albinism. Major HLH-directed drugs (etoposide, antithymocyte globulin, alemtuzumab, emapalumab, ruxolitinib) were administered to 66 of 76 patients who were symptomatic (86% first-line etoposide); 16 of 57 patients treated with etoposide and 3 of 9 with other first-line treatment received salvage therapy. HSCT was performed in 75 patients; 7 patients died before HSCT. Three-year probability of survival (pSU) was 82% (confidence interval [CI], 72%-88%) for the entire cohort and 77% (CI, 64%-86%) for patients receiving first-line etoposide. Compared with the HLH-2004 study, both pre-HSCT and post-HSCT survival of patients receiving first-line etoposide improved, 83% to 91% and 70% to 88%. Differences to HLH-2004 included preferential use of reduced-toxicity conditioning and reduced time from diagnosis to HSCT (from 148 to 88 days). Three-year pSU was lower with haploidentical (4 of 9 patients [44%]) than with other donors (62 of 66 [94%]; P < .001). Importantly, early HSCT for patients who were asymptomatic resulted in 100% survival, emphasizing the potential benefit of newborn screening. This contemporary standard-of-care study of patients with pHLH reveals that first-line etoposide-based therapy is better than previously reported, providing a benchmark for novel treatment regimes.
Gesehen am 13.01.2025